Implementasi penggunaan media video youtube terhadap keterampilan menulis teks prosedur kelas 4 SD - Fajri, Jahara Amarona; Indihadi, Dian; Rahayu Saputra, Erwin (COLLASE (Creative of Learning Students Elementary Education), 2025)
Writing is an activity carried out to express thoughts. One example of text created to express thoughts is procedure text. This study aims to determine the effect of implementing product making video media on procedural text writing skills in grade 4 elementary school students. This research uses quantitative methods with a one group pretest-posttest design. The research subjects were 4th grade elementary school students as an experimental class of 30 students consisting of 12 girls and 18 boys. Students are given learning treatment using YouTube video media. Research data was collected through a procedural text writing test. The research results showed that there was a significant difference between the pretest and posttest scores for grade 4 elementary school students. This shows that the implementation of product making video media is effective in improving procedural text writing skills in grade 4 elementary school students. Keyword: Video Media, Writing Skills, Procedure Text.